During cycling what limits maximum mechanical power output at cadences above 120 rpm - Hodson-Tole, E. F.; Blake, O. M.; Ollie, M.; Wakeling, J. M. (Medicine & Science in Sports & Exercise, 2020)
Purpose: A key determinant of muscle coordination and maximum power output during cycling is pedaling cadence. During cycling, the neuromuscular system may select from numerous solutions that solve the task demands while producing the same result. For more challenging tasks, fewer solutions will be available. Changes in the variability of individual muscle excitations (EMG) and multimuscle coordination, quantified by entropic half-life (EnHL), can reflect the number of solutions available at each system level. We, therefore, ask whether reduced variability in muscle coordination patterns occur at critical cadences and if they coincide with reduced variability in excitations of individual muscles.